A qualitative study on ASHA workers’ perspective on HPV self-sampling in Sikkim India - Roopa Hariprasad; Manikandan Srinivasan; Priyanka Ravi; Harki Tamang; Arpana Sharma; Sangeeta Pradhan; Kavitha Dhanasekaran (Scientific Reports)
Abstract Cervical cancer is a major public health concern in India, hampered by limitations in traditional screening methods and healthcare infrastructure. This study aimed to evaluate the feasibility and challenges of implementing Human Papillomavirus self-sampling (HPV) self-sampling, conducted by ASHA workers (Accredited Social-Health Activists) in Sikkim, India, using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework. In-depth interviews were conducted between February and May 2023 with ASHA workers involved in HPV self-sampling implementation within Sikkim. The data was analysed using qualitative methods and tagged under relevant RE-AIM categories. Twenty ASHA workers participated in the study. Facilitators included participant autonomy, positive community attitudes, and logistical advantages of home-based testing. ASHA workers’ efforts in health education, counselling, and community engagement were crucial. Successful implementation was supported by adequate training, community trust, and mobile technology for result transmission. Barriers included poor health literacy, logistical challenges for ASHA workers, and inadequate incentives. The study highlights the importance of tailored screening procedures, community engagement, and programmatic support in enhancing acceptance of HPV self-sampling. Addressing barriers requires multifaceted interventions at individual, community, and systemic levels.